A multimodal nanoparticles‐based theranostic method and system. (17th April 2022) - Gannot, Israel
Abstract: We propose a nanoparticles‐based system for the early detection of tumors, treatment under real‐time feedback, and monitoring. The building blocks of the system comprise a few modalities that are integrated into one powerful system which can operate at the patient's bedside in an outpatient clinic setting. The method relies on the unique characteristics of superparamagnetic nanoparticles. It takes advantage of their ability to produce acoustical signals under alternating magnetic fields (AMFs) and to produce heat under these same AMFs with different parameters. It utilizes the nanoparticles' coating for specific binding. The manuscript describes the various parts of this method for localization, source separation, confined heat elevation, triggering of cell death, and monitoring the response to treatment through fluorescence signaling. The entire system continues to evolve into a minimally invasive trans‐endoscopic set‐up. This article is categorized under: Diagnostic Tools > In Vivo Nanodiagnostics and Imaging Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Abstract : Proposed multi modal theranostic system concept.